PENDIDIKAN BERBASIS TEKNOLOGI - Alpian Alpian; Heliyana Zuriyati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of making this paper is to find out the meaning of Technology-Based Education the benefits of technology in the world of Education, as well as knowing the obstacles to the application of technology-based education. Technology is one of the keys to making education more prosperous. With technology-based education greatly influences the development of education both in the learning process and in the preparation of the curriculum, especially in building adequate educational facilities and infrastructure so that educational goals can be implemented. students to learn and get the information we need from anywhere, anytime, and from anyone. Constraints on the use of technology in schools include limited budgets for limited human resource learning facilities, hard work and lack of teacher competencies. Some benefits of the application of puzzleology in education, technology can help teachers teach, technology will trigger teacher creativity, help students learn, puzzleology can create learning activities that attract students easy to find learning resources, technology can improve school standards, make students have a broad insight